A survey of English language teachers' views of research - Kutlay, Nesrin (ELSEVIER SCIENCE BV, 2013)
The study aims to investigate the conceptions held by English language teaching instructors in a public university in Turkey and to specify the level of research engagement of teachers by either reading or conducting research. The data were collected form 52 English instructors through questionnaires and a subgroup of teachers were invited to interviews in order to shed light to the responses given in the questionnaire. The results showed that teachers evaluated the instances that are compatible with scientific research paradigm as research and the level of engagement in research was low. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ALSC 2012
Keywords: Teacher research; Educational research; Research engagement; English language teaching; Education & Educational Research; Linguistics